Slang Words in Providing Valuable Insights for Language Educators in Bali - Kadek Adyatna Wedananta; I Gst. Ayu P. Jesika Sita Devi N (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2024)
This study aims to find how slang words can provide valuable insights for language educators in Bali in enhancing language instruction and cultural understanding among students. The methodology used in this study was qualitative. This study was carried out in schools in Bali. Data for this study were gathered by documentation, interviews, and observation. This study resulted and discussed that slang words can provide valuable insights for language educators in Bali in enhancing language instruction and cultural understanding among students in the following ways, Cultural Relevance: Slang words are often deeply rooted in the culture and daily life of a community. Informal Communication: Slang words are predominantly used in informal settings, such as conversations among friends or peers. Nuances and Expressions: Slang words often convey specific nuances and expressions that may not be easily translated or understood through formal language instruction alone. Language Evolution: Slang words are dynamic and reflect the ever-evolving nature of language. Bridging Generational Gaps: Slang words are often associated with younger generations. It is recommended for further researcher to expand the topic.